Ethnological Classification Of The Customs And Rituals Of The Uzbek People Associated With The Birth Of A Child (Eurasian Journal of History, Geography and Economics, 2026)
This article provides a comprehensive analysis of the traditions and rituals of the Uzbek people associated with childbirth from the perspective of historical-ethnographic, sociocultural and transformational processes. The study covers beliefs and prohibitions related to pregnancy, rituals performed during childbirth, and traditional rituals after childbirth based on empirical materials and scientific sources. The results show that these traditions of the Uzbek people are not only a cultural heritage, but also a factor that strengthens social cohesion, family stability, and national identity in modern society. The article was developed in accordance with the requirements of IMRAD and is of theoretical and practical importance for dissertation research.